2019
DOI: 10.1101/753079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inverse correlation between heme synthesis and the Warburg effect in cancer cells

Abstract: Abstracts 12Cancer cells show a bias toward the glycolytic system over the conventional mitochondrial 13 electron transfer system for obtaining energy. This biased metabolic adaptation is called the Warburg 14 effect. Cancer cells also exhibit a characteristic metabolism, a decreased heme synthesizing ability. Here 15 we show that heme synthesis and the Warburg effect are inversely correlated. We used human gastric 16 cancer cell lines to investigate glycolytic metabolism and electron transfer system toward 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Based on these observations we thus did not find evidence for a substantial impact of the tumor types in WHO grade II gliomas. (4) Moreover, a current study demonstrated that highly glycolytic tumors do require less heme [ 33 ]. This mechanism might result in heterogeneity of the metabolic composition of especially high-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations we thus did not find evidence for a substantial impact of the tumor types in WHO grade II gliomas. (4) Moreover, a current study demonstrated that highly glycolytic tumors do require less heme [ 33 ]. This mechanism might result in heterogeneity of the metabolic composition of especially high-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…This fluorogenic dye indicates the overall ROS production. Some studies referred this marker is able to determine the hydroxyl, peroxyl and other ROS activities within the cell (37,38). Cells treated with rGO, PPIX and PPIX + rGO were washed thoroughly with PBS after 24 h of incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidants 2022, 11, x FOR PEER REVIEW 2 of 17 (PI3K/AKT/mTOR) are important in regulating several kinds of metabolisms in cancer cells [5][6][7][8][9][10].…”
Section: Oxidative Stress and Its Associated Metabolismsmentioning
confidence: 99%
“…Several factors that modulate metabolism may improve the anticancer therapeutic effects. Oxidative stress and phosphoinositide-3-kinase/AKT serine-threonine kinase/mechanistic target of the rapamycin kinase (PI3K/AKT/mTOR) are important in regulating several kinds of metabolisms in cancer cells [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%